Enhancing farmers’ income through technological interventions - Gadge, S. S.; Singh, Major (Indian Horticulture, 2019)
Vidarbha region in Maharashtra is known as non-traditional area foronion cultivation. The ICAR-DOGR, Pune, conducted demonstrations in2013 in Vidarbha region to increase area and production of onion. Seedand recommended cultural practices were provided to farmers. Trainingswere also given to farmers for increasing their knowhow and skill aboutimproved onion cultivation practices. The impact of adoption of ICARDOGRtechnologies was analyzed by undertaking a survey during 2015.The institute developed varieties, package of practices, broad bed furrowwith microirrigation and modified storage structures were adopted by90.84%, 70%, 62.5% and 44.17% farmers of Vidarbha region. The varietyhaving highest adoption was Bhima Shubhra (52.5%), followed by BhimaSuper (21%) and Akola Safed (6.5%).